How Ambiguous Is The Structural Ambiguity - Masda Surti Simatupang (Bina Nusantara University, 2007)
A word, phrase, or sentence is ambiguous if it has more than one meaning. The ambiguity, however, can be noticed if one really has a linguistic knowledge on how to analyze the phrase or sentence. Of the two kinds of ambiguity, lexical and structural, the latter is the one which is explored further in this paper. Structural ambiguity occurs when a phrase or sentence has more than one underlying structure. The phrase can be disambiguated by putting it in a sentence with some sort of formal signals which help the reader or hearer to recognize the sentence structure. Some of the signals include function words, inflections, affixes, stress, juncture, and punctuation. The rest of this paper discusses some types of structural ambiguity, how they differ, and some possible ways to resolve them.